2022
DOI: 10.3390/atmos13122049
|View full text |Cite
|
Sign up to set email alerts
|

Study on Thermal Storage Wall Heating System of Traditional Houses in Cold Climate Zone of China: A Case Study in Southern Shaanxi

Abstract: Solar energy has the advantages of being green, renewable, and energy-efficient. The use of solar energy in buildings can result in significant energy savings, and a great deal of practical and theoretical research has been conducted on solar buildings around the world. Southern Shaanxi belongs to a climate zone with hot summers and cold winters (HSCW). The mean room temperature is 4 °C, and it is lower than 2 °C at night, which greatly exceeds the thermal comfort range that the human body can bear. Aiming at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…[22,23]. Applied research on human thermal comfort mainly focuses on methods to regulate and improve the thermal comfort of people in spaces such as parks and residences [24][25][26]. A combination of questionnaires, field measurements, and statistical analyses have also been used to analyze the correlation between the comfort of typical human activities and the main weather parameters, and have confirmed that park microclimates could regulate human thermal comfort [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…[22,23]. Applied research on human thermal comfort mainly focuses on methods to regulate and improve the thermal comfort of people in spaces such as parks and residences [24][25][26]. A combination of questionnaires, field measurements, and statistical analyses have also been used to analyze the correlation between the comfort of typical human activities and the main weather parameters, and have confirmed that park microclimates could regulate human thermal comfort [27,28].…”
Section: Introductionmentioning
confidence: 99%